Comparison of different drying methods on Chinese ginger (Zingiber officinale Roscoe): Changes in volatiles, chemical profile, antioxidant properties, and microstructure - An, Kejing; Zhao, Dandan; Wang, Zhengfu; Wu, Jijun; Xu, Yujuan; Xiao, Gengsheng (Food chemistry, 2016)
•Intermittent microwave & convection drying was first applied in ginger drying.•A systematic exploration of energy consumption and quality retention was built.•Cluster analysis & PCA were used to evaluate the correlation of different dryings.•IM&CD is very promising in energy saving and quality retention for food drying. Nowadays, food industry is facing challenges in preserving better quality of fruit and vegetable products after processing. Recently, many attentions have been drawn to ginger rhizome processing due to its numerous health promoting properties. In our study, ginger rhizome slices were subjected to air-drying (AD), freeze drying (FD), infrared drying (IR), microwave drying (MD) and intermittent microwave & convective drying (IM&CD). Quality attributes of the dried samples were compared in terms of volatile compounds, 6, 8, 10-gingerols, 6-shogaol, antioxidant activities and microstructure. Results showed that AD and IR were good drying methods to preserve volatiles. FD, IR and IM&CD led to higher retention of gingerols, TPC, TFC and better antioxidant activities. However, FD and IR had relative high energy consumption and drying time. Therefore, considering about the quality retention and energy consumption, IM&CD would be very promising for thermo sensitive material.